Nitrogen transport and assimilation in tea plant (Camellia sinensis): a review - Zhang, Wenjing; Ni, Kang; Long, Lizhi; Ruan, Jianyun (Frontiers in Plant Science, 2023)
Nitrogen is one of the most important nutrients for tea plants, as it contributes significantly to tea yield and serves as the component of amino acids, which in turn affects the quality of tea produced. To achieve higher yields, excessive amounts of N fertilizers mainly in the form of urea have been applied in tea plantations where N fertilizer is prone to convert to nitrate and be lost by leaching in the acid soils. This usually results in elevated costs and environmental pollution. A comprehensive understanding of N metabolism in tea plants and the underlying mechanisms is necessary to identify the key regulators, characterize the functional phenotypes, and finally improve nitrogen use efficiency (NUE). Tea plants absorb and utilize ammonium as the preferred N source, thus a large amount of nitrate remains activated in soils. The improvement of nitrate utilization by tea plants is going to be an alternative aspect for NUE with great potentiality. In the process of N assimilation, nitrate is reduced to ammonium and subsequently derived to the GS-GOGAT pathway, involving the participation of nitrate reductase (NR), nitrite reductase (NiR), glutamine synthetase (GS), glutamate synthase (GOGAT), and glutamate dehydrogenase (GDH). Additionally, theanine, a unique amino acid responsible for umami taste, is biosynthesized by the catalysis of theanine synthetase (TS). In this review, we summarize what is known about the regulation and functioning of the enzymes and transporters implicated in N acquisition and metabolism in tea plants and the current methods for assessing NUE in this species. The challenges and prospects to expand our knowledge on N metabolism and related molecular mechanisms in tea plants which could be a model for woody perennial plant used for vegetative harvest are also discussed to provide the theoretical basis for future research to assess NUE traits more precisely among the vast germplasm resources, thus achieve NUE improvement.